FoxO1 Inhibitors: The Future Medicine for Metabolic Disorders? - Pandey, Anuradha; Kumar, Goru S.; Kadakol, Almesh; Malek, Vajir; Bhanudas Gaikwad, Anil (Current Diabetes Reviews, 2016)
FoxO1, one of the most widely expressed sub-families of the winged helix forkhead factors, is biologically ‘omni-functional’ owing to its far-flung roles in metabolism, cell cycle, tissue differentiation and development and oxidative stress response. The knowledge of involvement of FoxO1 in metabolic disorders has long been there, but the potential target remained underutilized due to unavailability of specific and potent inhibitors. The review provides an insight into the role of FoxO1 in orchestrating metabolic diseases’ pathogenesis (including diabetes, its secondary complications and obesity) and compiles the literature on FoxO1 inhibitors. The emergence of various natural molecules and synthesized small molecules like AS1842856 as FoxO1 inhibitors urges us to think further and decide the future course of drug development for the management of metabolic disorders.
Keywords: FoxO1 inhibitors